FIRE Study: Real-World Effectiveness and Safety of Ibrutinib in Clinical Practice in Patients with CLL and MCL - Caroline Dartigeas; Borhane Slama; Margaret Doyle; Christoph Tapprich; Claire Albrecht; Sandrine Dupuis; Robert Wapenaar; Charlotte Schmidt-Hieber; Veronique Leblond (Clinical Hematology International, 2022)
Abstract The FIRE study investigated the real-world effectiveness and safety of ibrutinib in prospectively observed patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL) and mantle cell lymphoma (MCL) in France. Patients were mostly relapsed/refractory with high-risk features. First-line CLL/SLL patients had del17p and/or TP53 mutations. In this interim analysis, the median follow-up time for patients with CLL/SLL and MCL was 17.7 and 15.1 months, respectively. In the effectiveness populations for CLL/SLL (n = 200) and MCL (n = 59), the median progression-free survival was not estimable and 12.4 months, respectively; the 12-month overall survival rates were 88.5% and 65.8%, respectively. Treatment-emergent adverse events of interest for patients with CLL/SLL (n = 202) and MCL (n = 59) included: infections and infestations (53.5% and 32.2%), major bleeding (5.0% and 5.1%), and atrial fibrillation (5.9% and 8.5%); 135 (66.8%) and 20 (33.9%) patients were continuing treatment at the time of data cutoff. Future analyses will report on longer-term follow-up (Trial registration: ClinicalTrials.gov, NCT03425591. Registered 1 February 2018—Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03425591 ).